2017
DOI: 10.1080/01635581.2017.1362446
|View full text |Cite
|
Sign up to set email alerts
|

The Protective and Immunomodulatory Effects of Fucoidan Against 7,12-Dimethyl benz[a]anthracene-Induced Experimental Mammary Carcinogenesis Through the PD1/PDL1 Signaling Pathway in Rats

Abstract: Fucoidan is a sulfated polysaccharide that is extracted from brown algae seaweed. This study was designed to evaluate the protective and immunomodulatory effects of dietary fucoidan on 7,12-dimethyl benz[a]anthracene (DMBA)-induced experimental mammary carcinogenesis in rats. Sixty Sprague-Dawley rats were randomly assigned to four equal groups: the control group (control group), the cancer model group (model group), and the F1 and F2 groups, which were fed fucoidan at concentrations of 200 and 400 mg/kg·body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…It has been shown, that ionogenic polysaccharides from an edible brown alga, Hijikia fusiforme (Hijiki), have a possible enhancing activity for macrophage-dependent suppression against tumor cell growth [ 55 ]. Finally, more recently, it has been shown that the immunomodulating effect is one of the possible mechanisms of the protective action of fucoidan against carcinogenesis of the breast [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown, that ionogenic polysaccharides from an edible brown alga, Hijikia fusiforme (Hijiki), have a possible enhancing activity for macrophage-dependent suppression against tumor cell growth [ 55 ]. Finally, more recently, it has been shown that the immunomodulating effect is one of the possible mechanisms of the protective action of fucoidan against carcinogenesis of the breast [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…The mice were free to access the standard dry diet as well as tap water ad libitum. All aspects of the experiment were conducted according to the Guide for the Care, and Use of Laboratory Animals (issued by the Ministry of Science and Technology of the People's Republic of China in 2006 [398]) and this research was approved by the Review Committee for the Use of Human or Animal Subjects of the Medical College of Qingdao University (Shi et al, 2017;Xue et al, 2017).…”
Section: Animal Model Preparationmentioning
confidence: 99%
“…Brown algae Sargassum fusiforme which dosage is twice than others, contains abundant polysaccharides such as fucoidan, algin, and so on. There are some evidences that fucoidan exerts anticancer activity through immune regulation [9,10]. In addition to polysaccharides, HMF contains quite a few of alkaloids, including dibenzylisoquinoline alkaloids dauricine and daurisoline which derived from Mertispermum dauricum, and steroid alkaloids solasonine and solamargine from Solanum nigrum.…”
Section: Introductionmentioning
confidence: 99%